Phase Characterization and Correction in a Hardware Implementation of an OFDM-Based System for VLC Applications - Juan Sebastian Betancourt Perlaza; Randy Lozada Dominguez; Enrique San Millan Heredia (IEEE Photonics Journal, 2023)
Orthogonal frequency-division multiplexing (OFDM) systems have been widely implemented in guided and non-guided communications. Even though they are becoming a standard for popular technologies such as WiFi, their implementation in newly emerging ones is still in evolution. As the number of connected devices increases, the radio frequency (RF) channel gets crowded. Here is where visible light communication (VLC) links gain interest. VLC offers a wireless alternative to RF with a trade-off between the necessity of line of sight with the offer of a free, highly secure, and immune to electromagnetic interference communication channel. This paper proposes a programmable software implementation of an OFDM system using a novel phase correction technique for VLC channels. The new equation considers two types of phase shifts, one that will be non-deterministic (has a random variation) and another that will be deterministic and, therefore, can be estimated and corrected. This second can be split into two: one that comes from the clock differences and has more impact on higher subcarriers, and the second that appears from the electronics of the link and will directly impact the symbols' phase. The main difference with current phase correction techniques is the identification and estimation of the deterministic noise specific to VLC systems. The deterministic noise impact all subcarriers equally and must be subtracted before the measure of the shift induced by the differences between the transmitter and receiver clocks. Another difference is that the analysis and tests have been done with data collected in an actual hardware implementation.